The marginalization of the elderly in Serbia - Đorđević, Anđela N. (Sociološki pregled, 2020)
The starting point of the paper is that the elderly in Serbia are marginalized, taking into account almost all dimensions of social exclusion, and that their exclusion from society is largely due to the poor economic situation in the country, as well as poor social policy which does not recognize the significant contribution that pensioners could make to society if given the opportunity and motivation for this type of activity. The aim of the paper is to determine whether the elderly (pensioners) in Serbia are marginalized or socially excluded. Then, if so, to determine in what dimensions their social exclusion manifests itself and to what extent. In addition, it is important to determine what factors lead to the marginalized position of pensioners, in order to look at the problem in its entirety. The paper gives an overview of theories and definitions explaining the problem of marginalization and social exclusion and the analysis of statistical data available at state institutions, such as the Statistical Office of the Republic of Serbia, the National Employment Service, the Pension and Disability Insurance Fund, etc. Survey results show that the elderly in Serbia are largely marginalized and socially excluded, especially in the field of social activities. Their social exclusion is a consequence of the poor economic situation in the country, poor financial situation of the retired people, poor health, inadequate education and qualifications, as well as governing stereotypes in Serbia about the elderly.